DETERMINAN TURNOVER INTENTION: STUDI KARYAWAN NON PEGAWAI NEGERI SIPIL DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - Abimanyu, Raditya Razindra; Suryatni, Mukmin; Nurmayanti, Siti (Jurnal Magister Manajemen, 2024)
This study examines the relationship between non-civil servant employees' intention to leave the Faculty of Economics and Business at the University of Mataram and job stress, organizational commitment, job satisfaction, and social support. Explanatory research is the kind of study that is employed. 75 non-civil servant employees of the University of Mataram's Faculty of Economics and Business were surveyed as part of the data collection process. PLS-SEM is the analytical tool employed. The analysis's findings indicate that: (1). job stress positively and significantly influences non-civil servant employees at the Unram Faculty of Economics and Business' intention to leave (2). The intention of non-civil servant employees at the University of Economics and Business to leave has a strong correlation with organizational commitment (3). The intention of non-civil servant employees at the Unram Faculty of Economics and Business to leave has no discernible relationship with job satisfaction (4). The intention of non-civil servant employees at the Unram Faculty of Economics and Business to leave has no discernible impact when it comes to social support